Zertalung und Hangbildung im Bereich der Süd-Ville - Fränzle, Otto (ERDKUNDE, 1969)
Within the framework of studies on erosion and valley evolution in the Rhine Massif and its borderlands the area NW of Bonn was mapped geomorphologically at 1:10 000. The 1:25 000 reduction of the field map is published here, the explanatory text being strictly limited to the above mentioned landforms and processes. The map is essentially morphographic (and morphometric), morphogenetic, and morphochronological, morphogeny being expressed by symbols and chronology by colour. A comprehensive description of the details of this map is under preparation. The Ville parallels the Rhine on its western side as a finger-like ridge, extending from the massif of the Eifel between Meckenheim and Bad Godesberg some sixty kilo meters north-north-westwards until it fades out in the undulating country north of the River Erft. Especially in its southern part it shows a marked asymmetry of its flanks. The western slope has preserved much of its original fault plane morphology whereas the eastern one constitutes a series of wide and largely dissected embayments. The main phases of dissection were the Mindel and Riss glacials cutting valleys more than 80 metres deep, whose cross pro files are in parts highly asymmetrical with the steeper slopes facing W to NW. The analysis of the correlative sediment cover of the slopes of lowest angle led to the conclusion that they were formed by both solifluction and periglacial slope wash, the latter becoming predominant in the final stages of evolution. By means of lithostratigraphic correlation a quite precise chronologic equivalency between the erosion of individual Ville streams and the sedimentation phases of the Rhenish Lower Middle Terrace (Drenthe) could be established; each stream proved to have had a morphodynamic activity of its own. The reasons are discussed and the general conclu sions drawn further corroborated by comparison with the results of pedostratigraphic studies in European loess areas. Periglacial slope wash during the Riss and the Mindel glacials also formed systems of glacis which are a characteristic morpologic feature of the Ville. During the Würm period a certain re-modelling of the landforms took place. Apart from local exceptions the processes involved varied in intensity according to the following general scheme: slope wash -> solifluction -> deposition of loess. In historic time human activity became the morphogenetic factor of prime importance.